The Effectiveness of Death Penal Sanction in Eradicating Corruption Crime in Indonesia Viewed from the Political Aspect of Law - Wahid, Mochamad Ananda Wyman; Hartiwiningsih (International Journal of Sustainability in Research, 2024)
In eradicating corruption in Indonesia, legal politics plays a role as a tool of approach by prioritizing the benefits of law by making legal discoveries or reforms according to social phenomena in society and the urgency of legal needs in terms of law enforcement. The politics of the death penalty in an effort to eradicate corruption is only regulated in Article 2 paragraph (2) of the Corruption Crime Law. Although in its development the DPR (government) has passed Law No. 1 of 2023 concerning the Criminal Code and included the crime of corruption in the new Criminal Code as a new breakthrough in eradicating the crime of corruption, in fact in its regulation the DPR (government) did not include the death penalty in the new Criminal Code for the crime of corruption.